External Factors and Their Impact on the Structure of the Abbasid Poem - Jawad kadhim, Haider ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The thematic structure of the Arabic poem has been characterized by two distinct patterns since the pre-Islamic era. The first pattern is that of the single-structured poem, in which the poet addresses a single subject. The second pattern is the multi-structured poem, where the poet tackles more than one subject, often two or three themes within a single composition. A variety of factors and influences contributed to shaping these patterns of poetic structure. In the Abbasid era, the single-structured poem was significantly influenced by religious and psychological factors, as well as certain intellectual movements such as Sufism and asceticism (zuhd). Additionally, urban development and environmental changes played a role in reshaping the thematic structure of poetry. For instance, poets abandoned traditional introductions like descriptions of ruins (al-muqaddima al-talliyya) and journeys, replacing them with themes more suited to their contemporary environment and lifestyle. On the other hand, the multi-structured poem was shaped by a commitment to classical traditions and an adherence to older poetic norms established by critics based on pre-Islamic poetry. This adherence was exemplified by figures such as Ibn Qutayba, who imposed upon later poets the framework of multi-thematic compositions.